Karakter Morfo-Fisiologi Daun Tanaman Kedelai (Glycine max (L.) Merr.) pada Cekaman Kekeringan: (Leaf Morpho-Physiological Characters of Soybean Plant (Glycine max (L.) Merr.) on Drought Stress - Pienyani Rosawanti (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2015)
Drought condition caused the changes in leaf morpho-physiological characters of soybean plant on drought stress. The purpose of this research was to study the leaf morpho-physiological characters of soybean plant on drought stress. Research was conducted in the Cikabayan greenhouse-IPB using complete randomized block design (RAKL) with 5 replications. First factor was soybean genotypes i.e. Slamet, Tanggamus and Wilis. Second factor was PEG i.e. PEG 0% and 20%. The drought stress was applied only at a vegetative phase. The result showed that drought stress with PEG simulation caused the changes in leaf morpho-physiological characters of soybean plant were trifoliat leaf number and leaf thickness. Leaf morpho-physiological characters of soybean that could be used as markers for adaptation under drought stress.